Teacher’s Higher Education and Students’ Achievements: A Research of the Perception of the Second Cycle Teachers in the New Juaben Area, Ghana - Yeyie Patrick (Social Education Research, 2022)
The study’s goal was to gather data on the perception of Social Studies teachers regarding whether a higher educational background or qualification of teachers results in higher students’ academic achievements in the New Juaben Senior High Schools in the Eastern Region. In this investigation, the researcher employed a semi-structured interview guide to obtain qualitative data. The researcher utilised simple random sampling, precisely the lottery method, to choose 24 respondents (24 teachers) for the study. This study looked at the perception of teachers teaching the subject within the New Juaben Municipality, Eastern Region, on whether a teacher’s higher qualification leads to higher students’ achievements. The majority of the social studies experts agreed with the school of thought that says a teacher’s higher education or qualification would lead to students’ academic achievements. A few social studies teachers disagreed with the notion that a teacher’s higher education or qualification leads to higher student achievements.